Considering the impact of universal newborn hearing screening and early intervention on language outcomes for children with congenital hearing loss. (1st October 2020) - Ching, Teresa Y. C.; Leigh, Greg
Abstract: Objective: In this paper, we draw on evidence to address the impact of earlier identification of congenital hearing loss through universal newborn hearing screening (UNHS) and the associated earlier access to interventions including cochlear implant (CI) technology on outcomes of children with hearing loss. Methods: Data from the Longitudinal Outcomes of Children with Hearing Impairment (LOCHI) study were analysed to examine the impact of UNHS and earlier intervention on language outcomes. The LOCHI study includes more than 450 deaf and hard of hearing Australian children whose hearing losses were identified variously through newborn hearing screening or later paths to confirmation and intervention. Results: Seventy-two percent of the screened group received hearing aid fitting before 6 months of age, which more than doubled the 32% in the non-screened group. On average, children who received earlier intervention achieved language at age 5 years commensurate with their typically developing peers. Children who do not have disabilities in addition to hearing loss and received their first CIs before age 12 months achieved language scores within the range of typically developing peers. Conclusion: Newborn hearing screening led to earlier intervention. Children who received earlier intervention achieved better outcomes than those who received later intervention.